2013
DOI: 10.1590/s1415-52732013000200001
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding promotion and support strategies based on Paulo Freire's epistemological categories

Abstract: OBJECTIVE: This study identified strategies for promoting breastfeeding involving pregnant women, breastfeeding women and actors of the social support network for the breastfeeding process. METHODS: This qualitative study was guided by action research and the focal group technique to collect data. Focal Group 1 consisted of four pregnant and six breastfeeding women; Focal Group 2 consisted of six family members; and Focal Group 3 consisted of thirteen health professionals. The focal groups were guided by the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 15 publications
0
5
0
11
Order By: Relevance
“…Thus, the social support network in which the family is inserted is also considered to be an opportunity for educational actions, since it is a source of support and exchange of knowledge, influencing the mother's decisions in the breastfeeding process (25) . Another prominent orientation in the reports of puerperal mothers was breast care, including sunbathing, cleaning and pumping, to avoid complications such as engorgement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the social support network in which the family is inserted is also considered to be an opportunity for educational actions, since it is a source of support and exchange of knowledge, influencing the mother's decisions in the breastfeeding process (25) . Another prominent orientation in the reports of puerperal mothers was breast care, including sunbathing, cleaning and pumping, to avoid complications such as engorgement.…”
Section: Discussionmentioning
confidence: 99%
“…It is necessary to value people's knowledge and experiences through dialogue, problematization and ethics to identify the opinions, feelings and impressions of social actors (7,25) . Moreover, in this study, the dissatisfaction of some puerperal women was also observed due to the lack of educational activities in the late and remote puerperium by primary care professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Os grupos de gestantes realizados nas unidades de saúde foram muito bem aceitos pelas puérperas, pois nos momentos do grupo recebiam dos profissionais orientações sobre a amamentação, esclareciam dúvidas e sentiam-se tranquilas, apoiadas e animadas durantes esses encontros (4,26) . Os grupos de apoio incentivam as nutrizes a amamentar e contribuem para a diminuição do desmame precoce (11,27,20) .…”
Section: Categoria Ii: Apoio Dos Profissionais De Saúdeunclassified
“…Estudos revelam a importância das ações educativas feitas pelas equipes de saúde na vida da mulher que está vivenciando a amamentação. As puérperas relataram que as ações educativas as ajudam guiar, incentivar, ensinar, orientar e esclarecer suas dúvidas sobre amamentação (22,26) . Da mesma forma, a sala de aconselhamento na unidade de saúde oportuniza momentos de Cogitare Enferm.…”
Section: Categoria Ii: Apoio Dos Profissionais De Saúdeunclassified
See 1 more Smart Citation